Profil Kohesivitas Kelompok Mahasiswa yang Bermukim di Perkotaan - Murniati AR; Mohammad Salehudin (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
This study aimed to find out how the cohesive profile of student groups living in urban areas is. This research uses a qualitative approach to literature (Library Research), namely by collecting data related to the theme of the research problem using Google Scholar and set 24 journal articles as data sources, then analyzed with descriptive qualitative. The results of the study found that the mobility of people moving to the city was unavoidable. It was the movement of students to continue their higher education in urban areas, approaching the college campus while students were studying. Group cohesiveness is an essential part for students who live in urban areas. Students are expected to be able to establish interactions between their fellow groups in order to achieve the group's goals. The cohesiveness of student groups living in urban areas can be seen from the organizations they participate in, both internal and external campus organizations. The level of cohesiveness will significantly affect organizational commitment. It depends on how far the group's goals are similar to the organization. Group cohesiveness is established through interactions in the form of good communication between group members. The existence of mutual liking and having a sense of mutual interest will make the group strong.Â Â